UPAYA MENINGKATKAN HASIL BELAJAR PAI MELALUI PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STAD PADA MATERI IMAN KEPADA KITAB ALLAH DAN RASUL SISWA KELAS XI IIS.2 SMA NEGERI 2 RAMBAH HILIR - UMI SALMAH (STKIP ROKANIA, 2019)
This study aims to improve student learning outcomes through the Application of STAD Type CooperativeLearning. This study is a Classroom Action Research (CAR) conducted in two cycles. Each cycle consists offour steps: namely, planning, action, observation, and reflection. The subject of this research is class XI IIS.2SMA 2 Rambah Hilir with the number of students 23 people. To get data in this study, researchers used twoinstruments, namely observation sheet activity and PAI test results from students. Student activities for eachindicator are given and analyzed by using percentage techniques. Improved learning outcomes can be seenfrom the number of students who complete the KKM set by the school. The results of data analysis in cycles one and two showed that there was an increase in student learning outcomes. The number of students whocompleted the KKM cognitive value increased from 56.52% in the previous UH to 65.22% in the first cycleand 82.61% in the second cycle. The activity value increased from 65.22% in the previous study to 66.96%in the first meeting and 80.87 in the second meeting of the first cycle and 86.09% in the first meeting and86.96% in the second meeting in the second cycle. In general it can be concluded that the Application ofCooperative Learning Type STAD can improve student learning outcomes.